Evaluating the appropriateness of blood component utilization in burns patients - J., Ravishankar; Y., Jagannathan S.; P., Arumugam; M., Chitra (International Journal of Research in Medical Sciences, 2016)
Background: Blood transfusion is a common intervention in critically ill surgical patients, especially Burns patients. But transfusions have potentially life threatening risks. The aim of the study was to evaluate the appropriateness of various blood components, utilized in Burns patients. Methods: Burns patient who were admitted at Burns ward, Government Kilpauk Medical College, Chennai, India with age more than 16 years, with 15-40% Total body surface area burns and had survived treatment were included for a period of one year (September 2014-August 2015). New York State health guidelines for RBC transfusion in Burns, Baxter’s original Parkland formula and platelet transfusion thresholds given by AABB were used to categorize appropriate transfusions from inappropriate transfusions. Results: A total of 122 burns patients who fulfilled the inclusion criteria were followed. 85 patients received 308 red cell units of which 64% were appropriate. 114 patients were transfused with 441 fresh frozen plasma units of which 47% were appropriate. One patient was transfused with platelet concentrate and all patients, who had their platelet count more than 10,000/μL, were not transfused. Conclusions: In our study, 64% of red blood cell transfusions and 47% of FFP transfusions were appropriate. Successful outcome of burns patients purely depends on proper wound care, along with appropriate use of fluids and blood components.